Verbalklammer und Trennbarkeit. Beitrag zur semantischen Begründung der Klammerfähigkeit bei den trennbaren Verbbildungen - Díaz Alonso, Javier (Revista de Filología Alemana, 2007)
The aim of this essay is to bring the verbal bracket, as the structural pattern of the german clause, together with the semantic characteristics of the separable verb formations. A very important part is played in this context by the content-related properties of composita and other verb formations inside and outside the frame of word formation, referring here to the semantic confrontation between determining words and primary words. These properties mean that separable verb formations are able to build a verbal bracket, whereas inseparable formations are clearly unable to do so. This essay deals with this topic and provides not only a general description of the phenomenon, but also a semantic explanation of the fact that separable verb formations can build a verbal bracket.
Keywords: Verbal Bracket; Separability; Meaning Determination; Word Formation